Convenient or Marketing matters? Unveiling the Determinants of Purchasing Decisions in Tokopedia E-Commerce - Sufyan, Izeldin Khalid; Pamuncak, Mohammad Bintang (Journal of Digital Marketing and Halal Industry, 2023)
This paper investigates the determinants of purchasing decision of Tokopedia e-commerce consumers with Gen-Z as a sample. This paper refers to Technology Acceptance Model (TAM) as theoretical framework, where the indicators use in this study combines both  convenient matter in purchasing at e-commerce such as Artificial Intelligence (AI) and marketing matters from both digital and non-digital marketing i.e., Islamic Marketing Ethics (IME). This paper employs Structural Equation Model-Pooled Least Square (SEM-PLS). The results show that AI and Digital Marketing (DM) have positive and significant relationship to influence consumers’ decision to purchase in Tokopedia. Meanwhile, IME has positive but non-significant relationship with purchase decision. This paper argues that this is due to the respondents’ knowledge of Sharia compliance in e-commerce transaction and lack of IME indicators socialization by Tokopedia, where Tokopedia already implement some indicators of IME in their feature such as Halal Corner. The result expects to contribute to development of theoretical and practical implication, particularly on Marketing matters both digital and Islamic marketing ethics.